(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2025)
This article provides an in-depth analysis of the current state of the anti-money laundering (AML) system in the banking sector of the Republic of Uzbekistan, with an assessment of readiness for artificial intelligence (AI) technology implementation. The study examines existing processes, technologies, gaps, and bottlenecks. An evaluation of technical infrastructure and human capital capacity is conducted. The analysis is supplemented by a review of international experience in AI implementation for AML purposes, including statistics, efficiency examples, and development stages. A comparative analysis and gap analysis for Uzbekistan are performed, based on which priority steps for AI utilization to enhance the effectiveness of the national AML system are proposed. The research is based on analysis of the regulatory framework, reports from international organizations (EAG, FATF), open-source data, and aggregated information on international practices.